Trajectory optimization for highly articulated robots based on sparsity-free local direct collocation - Cardona-Ortiz, Daniel; Arechavaleta, Gustavo (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we introduce a numerical optimal control scheme (NOCS) for generating dynamically feasible robot motions under several constraints while optimizing a give performance criterion. In particular, the NOCS transforms continuous optimal control problems into large-scale sparsity-free nonlinear programs (NLPs) by means of a dedicated strategy called the block indexation procedure (BIP). As a result, the optimized open-loop control law is obtained fast under limited memory allocation.
Keywords: robot trajectory optimization; numerical optimal control; direct collocation